Keputusan Pembelian Konsumen Pada Online Store - Roosita Meilani Dewi (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2017)
This study aims to analyze factors that affect consumer buying at online store. The data used in the research are primary data. The samples in this research consists of 100 respondents with the number of variables examined are 8 (eight) variables which consists of Cultures (X1), Social (X2), Personal (X3), Psychology (X4), Products (X5), Price (X6), Distribution (X7), Promotion (X8), and 38 items statement. Sampling technique used was convinience sampling. Methods of research carried out by using factor analysis, which aims to summarize or reduce the overall observation variables into several variables or new dimension, but variable or new dimension which is formed still present the main variables. The research found that these data provide the validity and reliability test results for factor analysis. Test results show that factor analysis of 8 (eight) variables there is only 1 (one) feasible factor, namely cultural factor. This shows that cultural factor is most dominant factor influencing purchase decisions it the online store. 75.73% variance was explained by factor that formed.